Subjective Objective Conditions for the Possibility of Punishment - Unead, Huda; Al-Shamry, Kazem (Journal of Legal Sciences, 2023)
Objective conditions for the possibility of punishment are legal or material facts –positive or negative that depart from the activity of the offender. The legislator comments on their subsequent verification on the formation of some crimes the possibility of.The application of punishment to the offender , but although they are facts of an object nature that approach and overlap with many systems and cases , they are distinguished by a certain subjectivity that differentiates them from each case that may seem similar or approach them.To clarify the ambiguity that may surround these conditions , Which may lead to confusion between them and what be similar to other cases due to the common effect that they have in common , which is the failure to impose punishment on the offender. Make it different and distinct from the objective conditions of punishment.